Dalit Consciousness in the works of Bama Faustina Soosairaj (International Journal of Food and Nutritional Sciences, 2021)
Literature produced from the Dalit writers is a new emerging trend in the Indian literary scenario often called as ‘Dalit Literature’ which has emerged to enable the development of new consciousness and identity among Dalits. Dalit writers write from several regional languages into English which contributed their segment of regional transformation to the new echo of just awakened Dalit consciousness. The idea of Dalit consciousness is a central concept in both the creation and evaluation of Dalit literature. Dalit consciousness has emerged during the late 19th and early 20th century in South India. It is a revolutionary consciousness which is based on the ideas of equality, liberty, justice and solidarity rather than pleasure. With the emergence of Dalit consciousness and Dalit voices across India during the last three decades the term has received considerable attention in the realm social sciences. Dalit consciousness opposes gender bias as it opposes regionalism, casteism and linguistic biases and issues. Bama Faustina Soosairaj (1958-), a Tamil novelist, is a leading name in the growing Dalit literary tradition in India. Her works are weapons of words, flags of consciousness, lamps of awareness and paths of empowerment. Some of her writings are Karukku (To wound the feelings), Sangati (Events) and Vanam (Revenge) which are the sources of awakening to the Dalits and oppressed of her community.